2020
DOI: 10.1186/s13089-020-00172-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound-guided thoracentesis in the intensive care unit: prevalence of mechanical complications

Abstract: Background: The use of thoracic ultrasound during thoracentesis reduces complications. The aim of this study was to determine the prevalence of complications for real-time ultrasound-guided thoracentesis performed by intensivists. As a secondary objective, the change in oxygenation before and after the procedure was evaluated. Patients and methods:An observational prospective study was conducted. A total of 81 cases of real-time ultrasound-guided thoracentesis performed by intensivists in the intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Even if pleural effusions are not frequent in COVID-19 patients, bedside thoracentesis can be tolerably performed with an echo-guided technique, to promote lung recruitment and ameliorate oxygenation and to reduce the incidence of peri-procedural complications ( Mercaldi et al 2013 ; Rodriguez-Lima et al 2020 ).…”
Section: Lus May Guide Therapeutic Decisions and Procedures In Intensmentioning
confidence: 99%
“…Even if pleural effusions are not frequent in COVID-19 patients, bedside thoracentesis can be tolerably performed with an echo-guided technique, to promote lung recruitment and ameliorate oxygenation and to reduce the incidence of peri-procedural complications ( Mercaldi et al 2013 ; Rodriguez-Lima et al 2020 ).…”
Section: Lus May Guide Therapeutic Decisions and Procedures In Intensmentioning
confidence: 99%
“…However, other authors include PC in the management in other pathologies, such as pleural effusions, Rodriguez Lima et al [13] with a prospective study including patients critically ill, with associated pleural effusions, showing a 1.2% complications rate, lesser than the reported in the literature, with comparable rates of success.…”
Section: Discussionmentioning
confidence: 96%
“…A prospective study by Rodriguez Lima et al 6 analyzed the use of real-time ultrasound guidance for thoracentesis and found that this procedure improved oxygenation and yielded fewer complications after the procedure (1.2%) compared with landmark technique aspiration of PF (10% to 18%). Another study by Helgeson et al 7 demonstrated that thoracenteses and chest tubes that used real-time ultrasound guidance, when compared with standard of care ultrasound-marked procedures in which the location of the procedure was found with ultrasound imaging but not used during the procedure, had a significantly lower rate of iatrogenic pneumothoraces.…”
Section: Discussionmentioning
confidence: 99%